2007
DOI: 10.1038/sj.mp.4002078
|View full text |Cite
|
Sign up to set email alerts
|

Proclivity to self-injurious behavior in MRL-lpr mice: implications for autoimmunity-induced damage in the dopaminergic system

Abstract: Systemic lupus erythematosus is frequently accompanied by psychiatric manifestations of unknown origin. Although damage of central neurons had been documented, little is known about neurotransmitter systems affected by the autoimmune/inflammatory process. Recent studies on lupus-prone MRL-lpr mice point to imbalanced dopamine function and neurodegeneration in dopamine-rich brain regions. We follow up on anecdotal observations of singly housed mice developing chest wounds. Compulsive grooming and/or skin biting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
(67 reference statements)
2
11
0
Order By: Relevance
“…We previously established that the two MRL substrains differ in responsiveness to neurotransmitter modulators, such as quinpirole, amphetamine, sertraline, and risperidone (42;44;54). In the present study, we observed discrepancies in responsiveness to MEM when nocturnal activity and climbing behavior were considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established that the two MRL substrains differ in responsiveness to neurotransmitter modulators, such as quinpirole, amphetamine, sertraline, and risperidone (42;44;54). In the present study, we observed discrepancies in responsiveness to MEM when nocturnal activity and climbing behavior were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several lines of evidence suggest aberrant dopaminergic neurotransmission in autoimmune MRL/lpr mice (42-45). We further examine this notion and the effects of MEM by employing a brief climbing test.…”
Section: Methodsmentioning
confidence: 99%
“…dopamine, serotonin, norepinephrine, glutamate) catabolism could also be involved in the pathogenesis of CNS damage in lupus. This hypothesis was studied in MRL-lpr strain by evaluating the neurotransmitter/metabolite levels in several brain regions [104,105,165]. MRL-lpr brains showed increased dopamine levels in the paraventricular nucleus (PVN) and the median eminence, decreased serotonin concentrations in the PVN and enhanced levels in the hippocampus, and decreased norepinephrine levels in the prefrontal cortex [83].…”
Section: Neuroinflammation-neurodegenerationmentioning
confidence: 99%
“…These include altered responses to the dopaminergic drugs amphetamine and apomorphine [52, 109, 132] and higher levels of apoptosis in the dopaminergic neurons in the nucleus accumbens and substantia nigra (thought to be involved in response to reward and anhedonia) in MRL/lpr mice [52, 109]. There are also decreased levels of serotonin in brain regions such as the hypothalamus, which regulate stress and response to appetitive stimuli (among other things) [133], and increased levels in the hippocampus [58].…”
Section: Introductionmentioning
confidence: 99%